Pengaruh model pembelajaran kolaboratif terhadap keterampilan menulis mahasiswa Program Studi Pendidikan Bahasa Jerman - Fatimah, Syarifah; Alamsyah, Alamsyah; Lestuny, Carolina (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2025)
Writing skills are one of the most challenging aspects of foreign language learning, including German. Students of the German Language Education Study Program, Faculty of Languages and Literature, Universitas Negeri Makassar, experience difficulties in producing grammatical and coherent texts. This study aims to determine the effect of applying the collaborative learning model on improving students’ writing skills. The research method used was an experimental design with a one-group pretest-posttest design. The participants were 16 second-semester students. The instrument used was a writing test assessed with a standardized rubric. Data analysis using a paired-sample t-test showed a significant improvement, with the average pre-test score increasing from 53.07 to 72.13 (tcount = 10.00 > ttable = 1.75). These findings indicate that the collaborative learning model is effective not only in enhancing the technical aspects of writing (grammar, vocabulary, and structure) but also in improving students’ motivation and social interaction. It is concluded that the collaborative learning model has a significant effect on students’ writing skills and can serve as an effective alternative teaching strategy in higher education.